Dynamic Changes in the Intracellular Association of Selected Rab Small GTPases with MHC Class II and DM during Dendritic Cell Maturation - Pérez-Montesinos, Gibrán; López-Ortega, Orestes; Piedra-Reyes, Jessica; Bonifaz, Laura C.; Moreno, José (Frontiers in Immunology, 2017)
Antigen processing for presentation by MHCII molecules requires the later to travel through the endocytic pathway together with its chaperons: the invariant chain (Ii) and DM. Nevertheless, the nature of the compartments where MHCII molecules travel to acquire peptides lack definition regarding molecules involved in intracellular vesicular trafficking, such as Rab small GTPases. We aimed to define which Rab proteins are present during the intracellular transport of MHCII, DM and Ii through the endocytic pathway on their route to the cell surface during dendritic (DC) cell maturation. We examined, by means three or four color of confocal microscopy, the association of MHCII, DM and Ii with Rab5, Rab7, Rab9 and Rab11 during the maturation of bone marrow-derived or spleen DC in response to LPS as an inflammatory stimulus. Prior to the stage of immature DC, MHCII migrated from diffuse small cytoplasmic vesicles, predominantly Rab5+Rab7- and Rab5+Rab7+ into a pericentriolar Rab5+Rab7+Rab9+ cluster, with Rab11+ areas. As DC reached the mature phenotype, MHCII left the pericentriolar endocytic compartments toward the cell surface in Rab11+ and Rab9+Rab11+ vesicles. The invariant chain and MHCII transport pathways were not identical. DM and MHCII appeared to arrive to pericentriolar endocytic compartments of immature DC through partially different routes. The association of MHCII molecules with distinct Rab GTPases during DC maturation suggest that after leaving the biosynthetic pathway, MHCII sequentially traffic from typical early endosomes to multivesicular late endosomes to finally arrive at the cell surface in Rab11+ recycling-type endosomes. In immature DCs, DM encounters transiently MHCII in the Rab5+Rab7+Rab9+ compartments, to remain there in mature DC.